Shuri. Wakanda forever - Okorafor, Nnedi; Ayala, Vita (Marvel Worldwide, Inc., 2020)
When her older brother T'Challa disappears, Wakanda's people turn to Shuri for leadership--but Shuri doesn't want to leave her science lab and her inventions. When the pressures of leading get too much, Shuri decides the best use of her time would be to head into space with Storm, Rocket Raccoon, and Groot to try to rescue her brother.